2017
DOI: 10.1159/000484327
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of End-Stage Renal Disease: A Swedish Adoption Study

Abstract: Background/Aims: The heritability of end-stage renal disease (ESRD) among adoptees has not been examined so far. By studying adoptees and their biological and adoptive parents, it is possible to differentiate between the genetic causes and environmental causes of familial aggregation. This nationwide study aimed to disentangle the genetic and shared environmental contribution to the familial transmission of ESRD. Methods: We performed a family study for Swedish-born adoptees (born between 1945 until 1995) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This was true not only for diseases with established high heritability but also entities, such as AKI, whose genetic basis is less pronounced 1 4 , 55 However, as reflected in our plot comparing AUCs using different sets of predictors, as one includes more measurable clinical risk factors for prediction, the incremental contribution of the PRS was smaller. In particular, much of the genetic risk was mediated through eGFR.…”
Section: Discussionmentioning
confidence: 78%
“…This was true not only for diseases with established high heritability but also entities, such as AKI, whose genetic basis is less pronounced 1 4 , 55 However, as reflected in our plot comparing AUCs using different sets of predictors, as one includes more measurable clinical risk factors for prediction, the incremental contribution of the PRS was smaller. In particular, much of the genetic risk was mediated through eGFR.…”
Section: Discussionmentioning
confidence: 78%
“…Our results demonstrate that, for a spectrum of kidney diseases, not only diseases with established high heritability, but also entities like AKI whose genetic basis is less pronounced, [1][2][3][4]22 PRS can now identify individuals with higher genetic risk for over 30 years of follow up, suggesting a potential role in further research and clinical medicine.…”
Section: Plasma Proteome As An Intermediate Traitmentioning
confidence: 90%
“…The heritability estimated by family studies are 30-75%. [1][2][3][4] Genomewide associations studies (GWAS) have grown rapidly in the last decade and identified numerous loci for kidney function, which gave rise to increasing attention to testing polygenic risk scores (PRS) as risk factors for kidney diseases risks. [5][6][7][8][9][10][11] However, previous PRS provided limited risk stratification for adverse kidney outcomes such as end-stage kidney disease (ESKD).…”
Section: Intruductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A family history of kidney disease is reported by 20–34% of adults with chronic kidney disease (CKD) [1-4]. Familial clustering of CKD, notably among patients with end-stage renal disease (ESRD), is well documented and largely attributed to genetic causes [3, 5-8] that may be under-recognized in clinical practice.…”
Section: Introductionmentioning
confidence: 99%